ESR and Raman studies of chemical bath deposited CdS : Ni films - U. Intatha (2018)
The CdS : Ni films were fabricated on glass substrates by chemical bath deposition method (CBD), where Ni concentrations are 0%, 10%, 20%, 30% and 40%. X-ray diffractometry (XRD), Raman spectroscopy and electron spin resonance (ESR) were employed to study the film structures. The XRD patterns revealed the presence of cubic CdS and trace of NiS. The Raman spectra were observed at 300 and 600 cm-1, corresponding to the first and second orders of the longitudinal optical phonon modes. Both results confirm that slightly lower order of crystallinity of CdS : Ni was found at the higher concentration of Ni. The ESR spectra showed the presence of F-type defects in CdS : Ni films. The band gaps of the samples were found to increase with the increase of Ni concentration. © 2008 World Scientific Publishing Company.